2003
DOI: 10.4161/cc.2.3.357
|View full text |Cite
|
Sign up to set email alerts
|

Flavopiridol Induces Mitochondrial-Mediated Apoptosis in Murine Glioma GL261 Cells via Release of Cytochrome c and Apoptosis Inducing Factor

Abstract: Glioblastoma (GBM) remains one of the most challenging solid cancers to treat due to its highly proliferative, angiogenic and invasive nature. The small molecule CDK inhibitor, flavopiridol, has demonstrated antitumor activity in human xenograft models and is currently in clinical trials showing efficacy in patients with advanced disease. We have developed an experimental animal model using the murine glioma GL261 cells as a novel in vivo system to screen potential therapeutic agents for GBM. Results of in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 25 publications
0
25
1
Order By: Relevance
“…Flavopiridol can trigger multiple apoptotic pathways depending on the type and stage of the target cell, thus circumventing drug-resistance mechanisms (42)(43)(44). Initial studies demonstrated that flavopiridol induced apoptosis via caspase 8 activation in some tumor cell types (42), whereas more recent evidence indicated that flavopiridol cytotoxic effects involved CytC release in others (33,55,56). Moreover, reports by Alonso et al (44) and Achenbach et al (42) demonstrated that flavopiridol apoptotic activity was exerted independently of both caspase 8 activation and CytC release in a panel of glioma and small-cell lung carcinoma cell lines, suggesting the implication of alternative, unidentified apoptotic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Flavopiridol can trigger multiple apoptotic pathways depending on the type and stage of the target cell, thus circumventing drug-resistance mechanisms (42)(43)(44). Initial studies demonstrated that flavopiridol induced apoptosis via caspase 8 activation in some tumor cell types (42), whereas more recent evidence indicated that flavopiridol cytotoxic effects involved CytC release in others (33,55,56). Moreover, reports by Alonso et al (44) and Achenbach et al (42) demonstrated that flavopiridol apoptotic activity was exerted independently of both caspase 8 activation and CytC release in a panel of glioma and small-cell lung carcinoma cell lines, suggesting the implication of alternative, unidentified apoptotic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…This agent is also a competitive inhibitor of adenosine triphosphate activity provoking down-expression of Bcl-2, AIF release and caspase-independent PCD. Flavopiridol has demonstrated a potent anti-tumor activity in chronic lymphocytic leukemia and solid tumors (84)(85)(86). A large number of clinical trials using this synthetic flavone are currently in progress.…”
Section: Therapeutic Strategies Targeting Aif-mediated Caspase-indepementioning
confidence: 99%
“…Permeabilization of the mitochondria, followed by cytochrome c release has previously been observed for transcriptional inhibitor flavopiridol (Newcomb et al, 2003). For this analysis, we used neuroblastoma cell lines NB-1691 and IMR32 and treated them with either DMSO or 3 mM of ARC.…”
mentioning
confidence: 99%